Comparison of Glasgow Coma Scale with Full Outline of Unresponsiveness Scale for predicting mortality among patients admitted in a Medical Intensive Care Unit (Bangladesh Critical Care Journal, 2022)
Background: For assessment of unconscious state in Medical Intensive Care Unit, physician mostly rely on Glasgow Coma Scale (GCS). But its verbal component has limitations in aphasic and intubated patient. More over its predilection ability to mortality is hardly challenged. The FOUR (Full outline of unresponsiveness) score, a new coma scale, evaluates 4 components: Eye, motor responses, brain stem reflexes and respiration. Aim of this study was to compare Full Outline of Unresponsiveness (FOUR) scale for prediction of mortality among patients admitted in Medical Intensive Care Unit (MICU) of a tertiary care hospital of Bangladesh with Glasgow Coma Scale (GCS).Objectives: To compare prediction of mortality between Glasgow Coma Scale (GCS) and Full Outline of Unresponsiveness (FOUR) scale.Methods: This is a prospective observational study was carried out in the Department of Critical Care Medicine, BIRDEM General Hospital to compare the mortality predilection in between FOUR score and GCS score. All consecutive adult unconscious patients over the age of 18 years were included in this study. Sedated patients were examined while they were not getting sedation or during routine sedation window period. Altered conscious level was examined by both GCS and FOUR scales. Data were collected using a check list containing demographic information, preexisting chronic illness, biochemical markers, imaging findings etc. Later patients were followed up and data regarding ICU stay, mortality and time of discharged from ICU were recorded. Both GCS and FOUR score were compared between survivor and non-survivor group and compared both score in between non-survivor group. Ultimately data were analyzed by using Statistical Package for Social Sciences (SPSS) software (version 20).Results: Total 105 unconscious patients were enrolled within the study after fulfilling inclusion & exclusion criteria. Among them 34 patients were survivor and 71 patient were non-survivor. The mean and SD of age in this study were 64 .55 ±14.65 years. The peak age distribution was (61-70) 39%. Among them 54.3 % (n=57) were male and 45.7 % (n=48) were female. DM (82.85%) was the most common comorbidity and the predominant diagnosis was Septic shock 33% followed by Ischemic stroke 29%, Meningo encephalitis 19.04 %, and Electrolytes imbalance 17.14%, Cardiogenic shock 12.38% etc. In both GCS and FOUR score their value significantly differ in case of both survival ([7.15± 1.56]; P